The Results of the Presidential Elections in Egypt in 2018 and of the Constitutional Referendum in 2019 - Volkov, Sergey N. (Africana Studia, 2020)
The Arab Spring emphasized the extraordinary importance of the youth policy for ensuring the national security in the countries of North Africa. President аl-Sisi placed the youth perspective in the center of his domestic policy. The article’s aim is to analyze the main tools of the youth policy of Abdel Fattah аl-Sisi, including policy in the field of party-building, tightened control over the activity of the non-governmental organizations, organization of the regular youth conferences, increasing efforts towards the solution of the main economic problems of the Egyptian youth – namely, a housing problem and the problem of the youth unemployment. The certain success achieved by the leadership of Egypt in these areas generally explains the results of the presidential elections in Egypt in 2018 and of the constitutional referendum of 2019 which are considered in this article. They testify that the opponents of the current government are mainly the residents of large cities, whose protest is not politically organized yet.